Validation of Australian Bureau of Meteorology High Resolution Wave Model (HI-WAM) - Coghlan, I R (UNSW Sydney, 2010)
The Water Research Laboratory (WRL) of the University of New South Wales has undertaken the first national assessment of the performance of the HI-WAM wave model developed by the Australian Bureau of Meteorology (BoM). The model was validated against wave buoy measurements from 18 locations around Australia over an 11 year period 1 (1997 to 2008). This high resolution, modified version of WAM was found to generally reproduce the overall natural variability of the sea state in terms of Significant Wave Height, Mean Wave Period and Wave Direction. However, while the HI-WAM model reproduces the overall natural patterns of the Australian climate and is considered to perform very well in moderate wave conditions, predictions for extreme measured wave heights are not considered to be suitable for engineering design purposes.
UNSW Water Research Laboratory Technical Report No. 237